(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Use of numerical formulations for solving engineering problems has always been essential in engineering. Thus, the use of structural analysis commercial or academic programs must be increasingly stimulated among future engineers, in the teaching of engineering schools, aiming to modeling common or more complex structural problems. In this context, this paper presents a numerical study (with the simulation of problems in computer) on reticulated structures that are used to support the billboards, seeking a better understanding of the behavior of the stresses internal load distribution, still aiming at identifying the most optimum arrangements for the beam of the structures. For this, we analyzed (by FTOOL® and Hyperworks® simulation software) some examples of reticulated structures support, like those used to support billboards panels, under the action of several loads, intending to reach contributions regarding the improvement of provision beam in favor of better distribution of internal loads acting on them. The development of this work presented many contributions to the scientific and professional training of the participants as well as for teaching of Engineering.